Representing unsegmented vessels using available vascular data for bioheat transfer simulation - Amare, Rohan; Bahadori, Amir A.; Eckels, Steven (Frontiers in Thermal Engineering, 2025)
IntroductionA primary challenge with voxel domains generated from imaging data is associated with voxel resolution. Due to the dimensional scale of blood vessels, not all vessels are captured in a given voxel resolution, leading to discontinuous blood vessels in the segmentation. Pre-capillary vessels like arterioles, which provide the highest resistance to blood flow, are often modeled with tissue as a porous domain due to resolution limitations. This results in a loss of information that could have been modeled if these vessels were segmented and modeled distinctly from the capillary bed.MethodsThis paper focuses on developing mathematical equations to calculate the flow resistance of unsegmented vasculature with reference to flow resistance of available segmented vascular data. A 3D vascular domain of 32 terminal vessels and five generations of bifurcation is simulated. Each generation is successively removed and substituted with the new flow resistance equations to analyze the error in heat transfer due to a lack of segmentation data.ResultsThe effect of using mathematical equations of flow resistance on bioheat transfer is analyzed. Two methods are proposed and demonstrated to show considerable error reduction in bioheat transfer.DiscussionVery high image resolution, which could allow modeling of pre-capillary vessels, increases the computational cost of the entire simulation domain. Instead, a mathematical representation of the pressure drop induced in these unsegmented blood vessels is used. The proposed methods show potential in reducing the error resulting from the lack of segmentation data, improving the accuracy of bioheat transfer simulations.